Optimising risk reduction: An expected utility approach for marginal risk reduction during regulatory decision making - Li, Jiawei W.; Pollard, Simon J. T.; Kendall, Graham; Soane, Emma; Davies, Gareth J. (Elsevier Science B.V., Amsterdam., 2009)
In practice, risk and uncertainty are essentially unavoidable in many regulation processes. Regulators frequently face a risk-benefit trade-off since zero risk is neither practicable nor affordable. Although it is accepted that cost-benefit analysis is important in many scenarios of risk management, what role it should play in a decision process is still controversial. One criticism of cost-benefit analysis is that decision makers should consider marginal benefits and costs, not present ones, in their decision making. In this paper, we investigate the problem of regulatory decision making under risk by applying expected utility theory and present a new approach of cost-benefit analysis. Directly taking into consideration the reduction of the risks, this approach achieves marginal cost- benefit analysis. By applying this approach, the optimal regulatory decision that maximizes the marginal benefit of risk reduction can be considered. This provides a transparent and reasonable criterion for stakeholders involved in the regulatory activity. An example of evaluating seismic retrofitting alternatives is provided to demonstrate the potential of the proposed approach. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Regulatory decision making Cost-benefit analysis ALARP Expected utility theory cost-benefit-analysis health alarp